The impact of child labor and school quality on academic achievement in Brazil - Márcio Eduardo G. Bezerra; Ana Lúcia Kassouf; Mary Arends-Kuenning (Institute for the Study of Labor (IZA), 2009)
We analyze the impact of child labor on school achievement using Brazilian school achievement test data from the 2003 Sistema Nacional de Avaliaç\~ao da Educaç\~ao Básica (SAEB). We control for the endogeneity of child labor using instrumental variable techniques, where the instrumental variable is the average wage for unskilled male labor in the state. Using our preferred OLS estimates, we find that child labor causes a loss in students' school achievement. Children and adolescents who do not work have better school performance than students who work. Up to two hours of work per day do not have a statistically significant effect on school performance, but additional hours decrease student's achievement. Differences in work conditions affect school performance. For high school students in Portuguese, compared to students who have schooling as their only activity, students who work only at home score 4 percent lower on the tests. Those students who only work outside the house are worse off than those who only work within the house, with test scores decreasing by 5 percent. Students who work both inside and outside the house have the lowest test scores of all the working conditions, decreasing by up to 7 percent.
urn:nbn:de:101:1-20090327294
Keywords: I21; J13; J22; O15; 330; Child labor; school achievement; Brazil; Kinderarbeit; Bildungsverhalten; Bildungsniveau; Bildungsabschluss; Brasilien